Potential roles of IL-38, among other inflammation-related biomarkers, in predicting post-percutaneous coronary intervention cardiovascular events - Kou, Lu; Yang, Ning; Dong, Bo; Qin, Qin (Frontiers in Cardiovascular Medicine, 2024)
Percutaneous coronary intervention (PCI), as a relatively rapid and effective minimally invasive treatment for coronary heart disease (CHD), can effectively relieve coronary artery stenosis and restore myocardial perfusion. However, the occurrence of major adverse cardiovascular events (MACE) is a significant challenge for post PCI care. To better understand risk/benefit indicators and provide post PCI MACE prediction, 408 patients with CHD who had undergone PCI treatment from 2018 to 2021 in Tianjin Chest hospital were retrospectively studied for their clinical characteristics in relation with the MACE occurrence during a 12-month follow-up. In the study, 194 patients had MACE and 214 patients remained MACE-free. Using uni- and multivariate regression analyses, we have shown that smoking history, elevated serum C-reactive protein levels (hs-CRP), and high haemoglobin levels A1c (HbA1c) are all independent risk factors for MACE after PCI. Furthermore, we have discovered that the serum level of IL-38, one of the latest members identified in the IL-1 cytokine family, is another predictive factor and is reversely related to the occurrence of MACE. The serum level of IL-38 alone is capable of predicting non-MACE occurrence in subcategorized patients with abnormal levels of hs-CRP and/or HbA1c.